INA617: Independent Studies / College of Built Environment - UiTM, College of Built Environment (2023)
The course introduces students to strategies for a research project. The exercise is geared to expose the students to research planning, various research methodology, analysis and writing strategies & format. Selected subject matter is used as an exercise in implementing the knowledge and skills in research works.